(untitled) (World Bulletin of Education and Learning, 2026)
This article analyzes the role and significance of Mannon Uygur’s style in the formation of stage speech. It highlights the expressiveness of the actor’s speech, the accuracy of pronunciation, and the role of speech culture in creating an image on stage. Based on the creative heritage of Mannon Uygur, the peculiarities of the development of stage speech are revealed. Its pedagogical approach and influence on contemporary theatrical art are also examined.